IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PREPARING THE 21ST CENTURY GENERATION TO WELCOME THE ERA OF SOCIETY 5.0 - Jayadi, Jayadi; Marini, Arita; MS, Zulela (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations born in the era of the Industrial Revolution 4.0, such as the Internet of Things, Artificial Intelligence, Big Data (large amounts of data), and robots to improve the quality of human life. This era is a new opportunity and a challenge for students to enhance soft skills in preparation for the future. The curriculum is the "soul" of Education. The curriculum needs to be evaluated dynamically and periodically following the times, especially science and technology. The curriculum is also prepared by considering the competencies the community and graduates need. The Merdeka Curriculum is one of the new policies of the Ministry of Education and Culture of the Republic of Indonesia, which is centred and follows students' needs (student-centred) and aims to realize an innovative learning process. The 21st century generation is expected to have 4C skills: critical thinking, communication, collaboration, and creativity. This study used a descriptive qualitative method. The results of this study were obtained from a review of several literatures. The study results explain how the Independent Curriculum implementation prepares the 21st-century generation to welcome the era of society 5.0.